Comparative study of the life cycle dependent post-translation modifications of protein synthesis elongation factor Tu present in the membrane proteome of streptomycetes and mycobacteria - Holub, M; Bezousková, S; Petrácková, D; Kalachová, L; Kofronová, O; Benada, O; Weiser, J (Folia microbiologica, 2010)
We present the results of analysis of membrane phosphoproteomes from individual morphological stages of Streptomyces coelicolor that reflect developmentally dependent heterogeneity and phosphorylation of intrinsic and externally added purified Strepomyces aureofaciens EF-Tu. Fast growing nonpathogenic Mycobacterium smegmatis was used as a non-differentiating actinomycetes comparative model. Streptomycetes membrane fraction was found to contain protein kinase(s) catalyzing phosphorylation of both its own and an externally added EF-Tu, whereas Mycobacterium membrane fraction contains protein kinase phosphorylating only its own EF-Tu.
Keywords: buněčná membrána; proteinkinasy; elongační faktor Tu; Peptide Elongation Factor Tu; fosforylace; posttranslační úpravy proteinů; Protein Processing, Post-Translational; Protein Kinases; Mycobacterium smegmatis; Streptomyces; Phosphorylation; Cell Membrane